A method for preparing hexagonal SrFe by liquid phase doping 12 O 19 Ferrite method and additives
Through the liquid phase doping method and C8H20O4Si additive, the problems of uneven composition and heterogeneous phase generation caused by the solid-state doping method are solved, and the magnetic properties of ferrite are significantly improved, which is suitable for efficient production.
Patent Information
- Application Number
- CN202311017131.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-14
AI Technical Summary
The existing solid-state doping methods can easily lead to uneven composition of ferrite raw materials and the formation of heterogeneous phases in the magnet, thereby limiting the improvement of magnetic properties.
Hexagonal SrFe12O19 ferrite was prepared by liquid phase doping method. By adding liquid C8H20O4Si as an additive at high temperature, the impurity phase generation was inhibited and the saturation magnetization of the sample was enhanced.
This method effectively improves the uniformity of raw material components, inhibits the formation of heterogeneous phases, improves the saturation magnetization and magnetic properties of ferrite, and is suitable for mass production.
Smart Images

Figure CN117049866B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of permanent ferrite preparation, and in particular to a method of preparing hexagonal SrFe by liquid phase doping. 12 O 19 Ferrite methods and additives. Background Art
[0002] Permanent ferrite has the characteristics of high resistivity, wide hysteresis loop, good chemical stability and corrosion resistance. Taking advantage of these characteristics, it is widely used in automotive electronics, microwave communications, aerospace, magneto-optics and microwave devices. my country is already the world's largest producer of permanent ferrite, but the technology for preparing high-performance permanent ferrite is still in the hands of developed countries. As an important type of permanent ferrite, the rapid development of the industry has promoted the high performance of SrM ferrite materials, and put forward higher performance requirements for traditional SrM ferrite permanent magnet materials.
[0003] At present, the research on improving the performance of ferrites is mainly focused on two aspects: synthesis methods and ion doping substitution. With the deepening of research, the direction of improving product performance through these two methods has encountered bottlenecks. Surveys show that the solid-state doping form commonly used in the prior art is not only prone to uneven composition in the raw materials, but may also form impure phases in the magnet, thereby greatly reducing the effect of improving the magnetic properties. For example, the invention patent with announcement number CN106745298B, entitled A method for enhancing the magnetic properties of M-type strontium ferrite, discloses a method of mixing and directly calcining the raw materials SrO, Fe2O3 and CeO2 to prepare SrFe 12-x Ce x O 19 Ferrite has an obvious Fe2O3 impurity peak in its XRD diffraction spectrum. Therefore, there is an urgent need for a liquid phase doping method to prepare hexagonal SrFe 12 O 19 Ferrite methods and additives are used to solve this problem. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing hexagonal SrFe by liquid phase doping. 12 O 19 The invention discloses a method and additive for producing ferrite, so as to solve the problem that the existing doping method easily leads to uneven raw material composition and formation of mixed phases in the magnet.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing hexagonal SrFe by liquid phase doping 12 O 19 The method of ferrite comprises the following specific steps:
[0006] Step 1: Prepare the Fe required for SrM ferrite 3+ / Sr 2+ Atomic ratio, weigh analytically pure Fe2O3 and SrCO3;
[0007] Step 2: Grind the weighed raw materials in a mortar and mix them evenly;
[0008] Step 3: Add liquid C8H 20 O4Si and grind and mix thoroughly;
[0009] Step 4: placing the ground and mixed powder in a mold for tableting to obtain a cylindrical sample;
[0010] Step 5: Take the sample, sinter it in a muffle furnace, and then cool it to room temperature to obtain a liquid-phase doped SrM ferrite block.
[0011] Preferably, in step 3, C8H 20 O4Si is used as an additive to suppress the formation of impurity phases and improve the saturation magnetization intensity of the sample.
[0012] Preferably, in step 2, C8H 20 The added mass of O4Si is 2-8% of the total mass of the weighed raw materials, and is added in a uniform dropwise manner.
[0013] Preferably, in step 1, Fe 3+ / Sr 2+ The atomic ratio is 10.
[0014] Preferably, in step 2, the grinding time is 10-30 min.
[0015] Preferably, in step three, the grinding time is 5-15 min.
[0016] Preferably, in step 4, the tabletting pressure is 10 MPa, and the pressure is maintained for 5 minutes.
[0017] Preferably, in step five, the sintering is performed by heating the material to 1100-1200° C. at a heating rate of 3-10° C. / min and calcining for 2 hours.
[0018] Another technical solution provided by the present invention is a method for preparing hexagonal SrFe 12 O 19 Ferrite additives, the additive is liquid ethyl orthosilicate (C8H 20 O4Si).
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. Liquid phase doping is used to prepare hexagonal SrFe12 O 19 The method of ferrite is simple and easy to operate, and the liquid phase is easy to flow, which improves the unevenness of the solid doping content in the raw materials, and the liquid phase C8H 20 The SiO2 obtained by decomposing O4Si at high temperature is more uniform and fine, has good sintering activity, is more conducive to grain growth and crystallization during sintering, and the saturation magnetization intensity of the sample is relatively high, thus playing the role of modifying SrM ferrite.
[0021] 2. Liquid phase doping is used to prepare hexagonal SrFe 12 O 19 Ferrite method and additives, using C8H 20 O4Si is a liquid substance that can decompose at high temperature to generate SiO2, CO2 and H2O. It is easy to add and mix evenly. Since CO2 and H2O can volatilize at high temperatures, there is less pollution during the reaction and it can be used for mass production.
[0022] 3. Liquid phase doping is used to prepare hexagonal SrFe 12 O 19 The method of preparing ferrite can also effectively inhibit the generation of impurity phases, which is helpful for preparing single-phase SrM ferrite. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Example 1 Addition of C8H 20 XRD pattern of O4Si SrM ferrite sample.
[0024] Figure 2 Example 1 Addition of C8H 20 Room temperature hysteresis loop of O4Si SrM ferrite sample.
[0025] Figure 3 Example 1 Addition of C8H 20 Typical SEM morphology of O4Si SrM ferrite.
[0026] Figure 4 Example 1 XRD spectrum of the SrM ferrite comparison sample with added SiO2.
[0027] Figure 5 Example 1 Room temperature hysteresis loop diagram of the SrM ferrite comparison sample with SiO2 added.
[0028] Figure 6 Typical SEM morphology of SrM ferrite with SiO2 added in Example 1.
[0029] Figure 7 Example 2 Addition of C8H 20 XRD pattern of O4Si SrM ferrite sample.
[0030] Figure 8 Example 2 Addition of C8H 20 Room temperature hysteresis loop of O4Si SrM ferrite sample.
[0031] Fig. 9 Example 2 Addition of C8H 20 Typical SEM morphology of O4Si SrM ferrite sample.
[0032] Fig.10 Example 2 XRD spectrum of the SrM ferrite comparison sample with added SiO2.
[0033] Fig.11 Example 2 Room temperature hysteresis loop diagram of the SrM ferrite comparison sample with SiO2 added.
[0034] Fig.12 Typical SEM morphology of SrM ferrite with SiO2 added in Example 2.
[0035] Fig.13 Example 3 Addition of C8H 20 XRD pattern of O4Si SrM ferrite sample.
[0036] Fig.14 Example 3 Addition of C8H 20 Room temperature hysteresis loop of O4Si SrM ferrite sample.
[0037] Fig.15 Example 3 Addition of C8H 20 Typical SEM morphology of O4Si SrM ferrite sample.
[0038] Fig.16 Example 3 XRD spectrum of the SrM ferrite comparison sample with added SiO2.
[0039] Fig.17 Example 3 Room temperature hysteresis loop diagram of the SrM ferrite comparison sample with added SiO2.
[0040] Fig.18 Typical SEM morphology of SrM ferrite with SiO2 added in Example 3. DETAILED DESCRIPTION
[0041] A method for preparing hexagonal SrFe by liquid phase doping 12 O 19 The method of ferrite comprises the following specific steps:
[0042] Step 1: Prepare the Fe required for SrM ferrite 3+ / Sr 2+atomic ratio (preferably 10), weigh analytically pure Fe2O3 and SrCO3;
[0043] Step 2: Put the weighed raw materials in a mortar and grind them thoroughly to mix evenly. The reference grinding time is 10-30 minutes;
[0044] Step 3: Add liquid C8H 20 O4Si is used as an additive to inhibit the formation of impurity phases and improve the saturation magnetization intensity of the sample. The sample is fully ground and mixed evenly. The reference grinding time is 5-15min. Preferably, C8H 20 The added mass of O4Si is 2-8% of the total mass of the weighed raw materials, and is added in a uniform dropwise manner;
[0045] Step 4: Place the ground and mixed powder in a mold for tableting to obtain a cylindrical sample; the reference tableting pressure is 10 MPa, and the pressure is maintained for 5 minutes;
[0046] Step 5: Take the sample and sinter it in a muffle furnace, then cool it to room temperature to obtain a liquid-phase doped SrM ferrite block; the sintering is preferably carried out by heating the temperature to 1100-1200°C at a heating rate of 3-10°C / min and calcining for 2 hours.
[0047] Example 1
[0048] First, according to the requirements for preparing SrM ferrite powder, 5g of raw materials are prepared to ensure that Fe 3+ / Sr 2+ The atomic ratio is 10, and 25mmol (4.22g) of Fe2O3 and 5mmol (0.78g) of SrCO3 are required. The powders weighed above are ground in a mortar for 20 minutes to obtain a uniform powder. Then, 4wt% of liquid C8H 20 O4Si (0.2g, 0.214ml) was evenly added to the powder and ground for 10 minutes. The mixture was transferred to a tableting mold and tableted. The tablet was kept at a pressure of 10MPa for 5 minutes to obtain a cylindrical sample. The pre-sintered cylindrical sample was placed in a muffle furnace and heated to 1200℃ at a heating rate of 5℃ / min for 2 hours. After sintering was completed, it was cooled to room temperature in the furnace and then taken out. The obtained sample was the SrM ferrite sample. Figure 1 The XRD pattern of the obtained SrM ferrite is compared with the XRD diffraction pattern of the pure M-type SrM ferrite standard card. No other impurity peaks are found, indicating that the prepared sample is a single-phase SrM ferrite. Figure 2 The room temperature hysteresis loop of the obtained SrM ferrite is shown in Figure 2. The shape and magnetic characteristics of the loop are typical hard magnetic characteristics of hexagonal strontium ferrite produced by the oxide method. It can be seen from the figure that the coercive force Hc is 228.10 kA / m, and the saturation magnetization intensity M s It is 63.03emu / g. Figure 3 This is a typical SEM morphology of the obtained SrM ferrite. From the figure, it can be seen that the grain size of the sample ranges from 1 to 4 μm, the grain boundaries are clear, and the grains are in a relatively typical flake shape.
[0049] SrM ferrite was prepared by the same method and experimental process as above, but the additive was C8H 20 O4Si was changed to directly add analytically pure SiO2 solid powder, the amount added was 0.0577g (i.e., with 0.2gC8H 20 The mass obtained by decomposition of O4Si is the same). Figure 4 The XRD diffraction pattern shows that in addition to the characteristic peaks of SrM ferrite, there is also a weak α-Fe2O3 impurity peak in the sample. Figure 1 It can be seen that adding C8H 20 O4Si can inhibit the formation of impurity phase. Figure 5 The room temperature hysteresis loop shows that the saturation magnetization M of SrM ferrite directly added with SiO2 s The value is 61.44emu / g, which is lower than that of liquid-phase doped SrM ferrite. Figure 6 The SEM morphology shows that the grain size of the sample is concentrated around 0.9 μm, which is significantly smaller than that of the attached Figure 3 Add C8H 20 Samples of O4Si.
[0050] Example 2
[0051] In this embodiment, C8H 20 The preparation method of the two samples of O4Si and SiO2 is the same as that of Example 1, and the changed parameters are: the sintering temperature is 1100°C.
[0052] Addition of C8H 20 O4Si SrM ferrite sample, attached Figure 7 The XRD diffraction pattern shows that there is no diffraction peak of any impurity other than SrM ferrite, indicating that a single-phase hexagonal M-type SrM ferrite has been prepared. Figure 8 The room temperature hysteresis loop of the obtained sample shows typical hard magnetic properties. s While remaining basically unchanged (62.68emu / g), the coercive force H c Increased to 340.77kA / m, an increase of 49.40%. Fig. 9The typical SEM morphology of the obtained sample shows that the grains are fine and evenly distributed. Compared with Example 1, due to the lower sintering temperature, the grain size is significantly smaller than that of the SrM ferrite prepared at 1200°C, and is basically maintained at about 1μm, which is near the single domain critical size of SrM ferrite. This is the reason why H c The main reason for the significant increase.
[0053] For the SrM ferrite sample with direct addition of SiO2, Fig.10 The XRD diffraction spectrum of the sample contains the characteristic peaks of SrM ferrite and the impurity peaks of α-Fe2O3. Figure 7 , which can also explain the addition of C8H 20 O4Si can inhibit the formation of impurity phase. Fig.11 The room temperature hysteresis loop of the obtained SrM ferrite is shown in Figure 2. c and saturation magnetization M s They are 357.38 kA / m and 56.90 emu / g respectively. Figure 8 It can be seen that although adding C8H 20 The coercivity of O4SiSrM ferrite sample is H c Slightly lower than that of direct addition of SiO2, but its M s There was a significant increase (10.16%). Fig.12 The SEM morphology shows that the grain size of the sample is concentrated around 0.8 μm, which is also lower than that of the attached Fig. 9 The average grain size in the nanostructured carbon nanotubes is very close to the single domain critical size, so the coercivity is relatively high.
[0054] Example 3
[0055] In this embodiment, C8H 20 The preparation methods of the two samples of O4Si and SiO2 were the same as those in Example 1, and the changed parameters were the addition of C8H 20 The amounts of O4Si and SiO2 were 0.3 g (6 wt%, 0.321 ml) and 0.0865 g, respectively.
[0056] Addition of C8H 20 O4Si SrM ferrite sample, attached Fig.13 The XRD diffraction pattern is shown in Figure 1. There is no diffraction peak of any impurity other than SrM ferrite in the figure, indicating that a single-phase hexagonal M-type SrM ferrite has been prepared. Fig.14 The room temperature hysteresis loop of the obtained SrM ferrite is shown in Figure 2. c is 228.5kA / m, and the saturation magnetization intensity M s The value is 63.02emu / g, and C8H is added in Example 1. 20The magnetic properties of O4Si and SrM ferrite samples are equivalent. Fig.15 This is a typical SEM morphology of the obtained SrM ferrite. The sample is irregular in shape, the grain surface is smooth without obvious defects, and the grain size ranges from 1 to 3 μm.
[0057] For the SrM ferrite sample with direct addition of SiO2, Fig.16 From its XRD diffraction spectrum, it can be seen that the sample still contains the characteristic peaks of SrM ferrite and α-Fe2O3 impurity peaks, which further illustrates that C8H 20 O4Si can inhibit the formation of impurity phase. Fig.17 is the room temperature hysteresis loop of the sample, and its coercive force H c is 297.19 kA / m, and the saturation magnetization intensity M s It is 57.96emu / g. Fig.14 , add C8H 20 The coercivity of O4SiSrM ferrite sample is H c The decrease is greater than that of direct addition of SiO2, but its M s There was a significant increase (8.73%). Fig.18 The SEM morphology shows that the average grain size of the samples is basically below 1 μm, and very few reach 1 μm, which is much lower than that of the attached Fig.15 The average grain size in.
[0058] Based on the above three embodiments, it is not difficult to see that the liquid phase C8H 20 O4Si instead of SiO2 as additive to prepare hexagonal SrFe 12 O 19 The ferrite method can stably improve the saturation magnetization intensity of the product without changing other conditions. The average grain size is large, and the effect of suppressing impurity phase can be seen from the comparison of the XRD patterns of the samples.
[0059] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
[0060] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for preparing hexagonal SrFe by liquid phase doping 12 O 19 A method of producing a ferrite, characterized in that The specific steps include: Step 1: Prepare hexagonal SrFe 12 O 19 Fe required for ferrite 3+ / Sr 2+ Atomic ratio, weigh analytically pure Fe2O3 and SrCO3; Step 2: Grind the weighed raw materials in a mortar and mix them evenly; Step 3: Add liquid C8H 20 O4Si and grind and mix well, add C8H 20 O4Si is used as an additive to suppress the formation of impurity phases and improve the saturation magnetization of the sample; Step 4: placing the ground and mixed powder in a mold for tableting to obtain a cylindrical sample; Step 5: Take the sample and sinter it in a muffle furnace and then cool it to room temperature to obtain liquid-phase doped hexagonal SrFe 12 O 19 Ferrite block.
2. The method of preparing hexagonal SrFe by liquid phase doping according to claim 1 12 O 19 A method for producing a ferrite, characterized in that: In the step 3, C8H 20 The added mass of O4Si is 2-8% of the total mass of the weighed raw materials, and is added in a uniform dropwise manner.
3. The method of preparing hexagonal SrFe by liquid phase doping according to claim 1 12 O 19 A method for producing a ferrite, characterized in that: In the step 1, Fe 3+ / Sr 2+ The atomic ratio is 10.
4. The method of preparing hexagonal SrFe by liquid phase doping according to claim 1 12 O 19 A method for producing a ferrite, characterized in that: In the step 2, the grinding time is 10-30 min, and in the step 3, the grinding time is 5-15 min.
5. The method of preparing hexagonal SrFe by liquid phase doping according to claim 1 12 O 19 A method for producing a ferrite, characterized in that: In the step 4, the tabletting pressure is 10 MPa, and the pressure is maintained for 5 minutes.
6. The method of preparing hexagonal SrFe by liquid phase doping according to claim 1 12 O 19 A method for producing a ferrite, characterized in that: In the step 5, the sintering is performed by heating the temperature to 1100-1200° C. at a heating rate of 3-10° C. / min and calcining for 2 hours.
Citation Information
Patent Citations
A method for enhancing the magnetic properties of m-type strontium ferrite
CN106745298B
Method for preparing ferrite by using nanometer MnZn ferrite powder
CN108046791A
Method for improving remanence of strontium ferrite pre-sintered material
CN108101528A
Cited By
Preparation method of liquid biphase co-doped hexagonal M-type strontium ferrite
CN120854103A